2004
DOI: 10.1016/j.febslet.2004.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II associated carbonic anhydrase activity in higher plants is situated in core complex

Abstract: The thylakoid membrane containing photosystem II (PSII membranes) from pea and wheat leaves catalyzed the reaction of CO 2 hydration with low rate, which increased after their incubation either with Triton X-100, up to Triton/chlorophyll ratio 1:1, or 1 M CaCl 2 . The presence of the inhibitor of CAs, p-aminomethylbenzensulfonamide (mafenide), at the start line in the course of electrophoresis of PSII membranes solubilized by n-dodecyl-b-maltoside (DM) decreased the amount of PSII core complex in the gel. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Lu and Stemler (2002) and Moskvin et al (2004) found high CA activity of the core complex of the PSII from maize and pea, respectively. Khristin et al (2004) showed that a high molecular mass carrier of CA activity in the PSII-membranes appeared as a part of the core complex of the PSII, and discussed the possibility that such an activity could be the property of a specific structure, and not of an individual protein. This proposition may be compared to the presence of only one peak upon Triton treatment of PSII-membranes (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Lu and Stemler (2002) and Moskvin et al (2004) found high CA activity of the core complex of the PSII from maize and pea, respectively. Khristin et al (2004) showed that a high molecular mass carrier of CA activity in the PSII-membranes appeared as a part of the core complex of the PSII, and discussed the possibility that such an activity could be the property of a specific structure, and not of an individual protein. This proposition may be compared to the presence of only one peak upon Triton treatment of PSII-membranes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Later, Lu and Stemler (2002) stated that two sources of CA activity could be associated with PSII in maize mesophyll chloroplasts. Khristin et al (2004) found that at least a part of the CA activity of thylakoid membrane fragments enriched with PSII (PSII-membranes) from wheat was connected with the core complex of this photosystem. Ignatova et al (2006) presented evidence of the presence of two types of CA activity in the PSIImembranes isolated from pea leaves, and found that one of the CA activities was associated with a low molecular mass protein.…”
Section: Introductionmentioning
confidence: 99%
“…Strictly speaking, however, these data are still compatible with a catalytic role of bicarbonate if the equilibrium between water, CO 2 , and bicarbonate is rapidly installed, as mediated, for example, by a carbonic anhydrase (CA; Silverman and Tu, 1975;Tu and Silverman, 1975). An intrinsic CA activity is indeed linked to the core and/or extrinsic proteins of PSII (Dai et al, 2001;Stemler, 2002;Villarejo et al, 2002;Khristin et al, 2004). The above-cited mass-spectrometric experiments were not designed to specifically address the bicarbonate question, and therefore the CA activity was not assessed in detail.…”
mentioning
confidence: 99%
“…The evidence in favour of the presence of two sources of CA activity in PSII-membranes was also obtained for pea [58,64] and for arabidopsis [62]. The CA activity appeared in solution after treating PSII-membranes either with salts in high concentration [58,70] or with detergents [64], but a significant part of the CA activity remained in PSII membranes [58,64,70,71,72]. The presence of two sources of CA activity in PSII was also revealed after native electrophoresis of detergent-treated PSII membranes from pea and arabidopsis: CA activity was detected in the gel band containing the low molecular mass proteins as well as in the upper gel area containing proteins associated with the PSII core complex [62,64,73].…”
Section: Carbonic Anhydrases In Chloroplastsmentioning
confidence: 93%